2019
DOI: 10.1177/0391560319834490
|View full text |Cite
|
Sign up to set email alerts
|

MRI ultrasound fusion biopsy in prostate cancer detection: Are randomized clinical trials reproducible in everyday clinical practice?

Abstract: The aim of this study was to evaluate the performance of multiparametric magnetic resonance imaging (mpMRI)-ultrasound (US) fusion-targeted biopsies (TB) in men with primary and repeated biopsies comparing the cancer detection rate (CDR) of random biopsies (RB) + TB versus only TB. Methods: The present study is a real-life study on patients with primary and prior negative prostate biopsies with suspicious PCa. A total of 130 men with prostate-specific antigen (PSA) value >2.5 ng/dL and/or abnormal digital rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Only a few studies have concluded that bpMRI can be used instead of mpMRI to guide MRI/US fusion-targeted biopsy [ 48 ]. Some authors argue that, while mpMRI-ultrasound fusion biopsy is associated with high cancer detection rates in clinically significant PCa, it has some limitations that TRUS biopsies alone do not have [ 74 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have concluded that bpMRI can be used instead of mpMRI to guide MRI/US fusion-targeted biopsy [ 48 ]. Some authors argue that, while mpMRI-ultrasound fusion biopsy is associated with high cancer detection rates in clinically significant PCa, it has some limitations that TRUS biopsies alone do not have [ 74 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis from 13 studies showed the overall pooled sensitivity of PSMA PET/CT for staging in prostate cancer were 92% (30). MRI-US fusion-guided biopsies detected more clinically significant cancers than standard biopsy techniques (12,17,(31)(32)(33). In our study, prostate biopsies performed on targeted 18 F-DCFPyL PET-positive lesions of 55 patients had a high detection rate (51/55, 92.7%) of prostate cancer, and a high proportion (85.5%, 47/55) were clinically significant prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the higher the prostate lesion PI-RADS scores in patients, the greater the value of TRUS/MRI fusion-guided biopsy. 5,7 However, the use of PI-RADS for lesion scoring is mainly based on qualitative images of different Mp-MRI sequences and there is a lack of objective quantitative parameters. Hence, the results tend to be affected by the experience of the interpreting radiologist.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the selection of suitable proatate lesions for TRUS/MRI fusion‐guided biopsy is worthy of our attention. Previous studies have shown that the higher the prostate lesion PI‐RADS scores in patients, the greater the value of TRUS/MRI fusion‐guided biopsy 5,7 . However, the use of PI‐RADS for lesion scoring is mainly based on qualitative images of different Mp‐MRI sequences and there is a lack of objective quantitative parameters.…”
Section: Introductionmentioning
confidence: 99%